Democracy Does Not Cause Growth: The Importance of Endogeneity Arguments - Julia Ruiz Pozuelo; Amy Slipowitz; Guillermo Vuletin (Inter-American Development Bank (IDB), 2016)
This article challenges recent findings that democracy has sizable effects on economic growth. As extensive political science research indicates that economic turmoil is responsible for causing or facilitating many democratic transitions, the paper focuses on this endogeneity concern. Using a worldwide survey of 165 country-specific democracy experts conducted for this study, the paper separates democratic transitions into those occurring for reasons related to economic turmoil, here called endogenous, and those grounded in reasons more exogenous to economic growth. The behavior of economic growth following these more exogenous democratizations strongly indicates that democracy does not cause growth. Consequently, the common positive association between democracy and economic growth is driven by endogenous democratization episodes (i.e., due to faulty identification).
hdl:11319/7758
Keywords: E02; E20; N40; 330; Democracy; Growth; Democratic transitions; Endogeneity